Novel Insights for Systemic Inflammation in Sepsis and Hemorrhage - Bolin Cai; Edwin A. Deitch; Luis Ulloa (Mediators of Inflammation)
The inflammatory responses in sepsis and hemorrhage remain a major cause of death. Clinically, it is generally accepted that shock in sepsis or hemorrhage differs in its mechanisms. However, the recognition of inflammatory cytokines as a common lethal pathway has become consent. Proinflammatory cytokines such as tumor necrosis factor (TNF) or high-mobility group box1 (HMGB1) are fanatically released and cause lethal multiorgan dysfunction. Inhibition of these cytokines can prevent the inflammatory responses and organ damage. In seeking potential anti-inflammatory strategies, we reported that ethyl pyruvate and alpha7 nicotinic acetylcholine receptor (alpha7nAChR) agonists effectively restrained cytokine production to provide therapeutic benefits in both experimental sepsis and hemorrhage. Here, we review the inflammatory responses and the anti-inflammatory strategies in experimental models of sepsis and hemorrhage, as they may have a consistent inflammatory pathway in spite of their different pathophysiological processes.